Practices and attitudes of dentists regarding the use and phase-out of dental amalgam fillings: compliance with EU regulations and the Minamata Convention - Vanja Usenik; Davor Kontić; David Kocman; Milena Horvat (Zdravniški Vestnik, 2025)
Background: This study examines the responses of 171 dentists to a comprehensive questionnaire to understand the current practice regarding the use and phase-out of dental amalgam. It assesses compliance with EU Regulation 2017/852 and the Minamata Convention, exploring factors associated with material choice, dentists’ awareness of regulations, and the use of amalgam separators. The study also identifies challenges and proposes support mechanisms to facilitate a smoother transition to mercury-free dentistry.